Citrates of metals in technology of diabetic bakegoods - Drobot, Vira; Prokhorova, Nadezhda; Shevchenko, Anastasiia (My University, 2015)
The work is devoted to the research of the impact of calcium, magnesium, zinc, iron citrates and their mixture on technological process of bakery products for diabetics. The effect of citrates on the yeast fermentative activity, structural and mechanical properties of dough and quality of finished products is set.
Keywords: citrates of metals; fructose; mineral substances; bread; diabetes; technology; цитрати металів; фруктоза; мінеральні речовини; хліб; діабет; технологія; кафедра технології хлібопекарських і кондитерських виробів